PENINGKATAN AKTIVITAS SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI SEKOLAH DASAR - Hana, Hana; Salimi, Asmayani; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ The general problem in this study whether using the problem based learning model can increase student activity in class III civic education subjects SDN 06 Pereges, Seluas District? The general objective of this study is to improve student learning activities by using a problem based learning model on the subjects of class III citizenship education at SDN 06 Pereges, Seluas District. This study uses descriptive methods with the form of classroom action research, and the nature of research is collaborative. The research setting took place at SDN 06 Pereges, Seluas Subdistrict, with research subjects, namely class III B students totaling 24 people. Data collection techniques used are interview techniques, direct observation techniques, measurement techniques with data collection tools namely observation sheets. The data collected is analyzed with percentage and average calculations.This research was conducted in 3 cycles. The ability of teachers to design learning in cycle 1 obtained an average score of 3.39 with a good category, in cycle 2 experienced an increase of 0.25 to 3.64 with a very good category, and in cycle 3 had an increase of 0.13 to increase to be 3.77 with a very good category. The ability of teachers to carry out learning in cycle 1 obtained an average score of 3.45 with a good category, in cycle 2 experienced an increase of 0.11 to 3.56 very well, and in cycle 3 had an increase of 0.25 so it increased to 3.81 with a very good category. Student activity in cycle 1 obtained a percentage of 57.82%, in cycle 2 it increased by 7.36% to 65.18%, and in cycle 3 also increased by 13.54% to 78.72%. With the implementation of the problem based learning model in learning civic education can improve student learning activities.Â Keywords : Learning Activities, Problem Based Learning Â